Use of motivational interviewing by advocates in the context of an elder abuse response intervention: the RISE project - MacNeil, Andie (Journal of family violence, 2024)
Purpose: Despite the increasing number of elder abuse and self-neglect (EASN) cases, many older adults are reluctant to engage with formal support services, such as Adult Protective Services (APS). This study examined the use of motivational interviewing (MI) by advocates, as a component of a larger EASN intervention, RISE (Repair Harm, Inspire Change, Support Connection, Empower Choice), implemented in partnership with APS. Advocates applied MI as part of RISE to help clients explore and resolve ambivalence around pursuing change and ultimately enhance service engagement. Methods: This study conducted qualitative interviews and a focus group with all RISE advocates (n = 4) to understand how MI is applied in the context of an EASN intervention with older adult clients. A descriptive phenomenological approach involving two independent assessors was used to code verbatim transcripts into themes. Results: Three domains were identified: (1) therapeutic relationship, which describes the importance of foundational relationship building in MI to support older adults who have experienced EASN; (2) techniques, which refers to MI strategies advocates apply and adapt in the context of EASN intervention; and (3) implementation challenges, which reflects the difficulties advocates encounter when using MI in cases of EASN. Conclusions: The experiences of advocates suggest MI is a beneficial and amenable approach to help older adults who have experienced EASN navigate issues of ambivalence and explore their motivation for change. This study represents the first in-depth exploration of MI in the context of EASN intervention.